2021
DOI: 10.1001/jamanetworkopen.2021.40584
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Inflammation During Pregnancy With Birth Outcomes and Infant Growth Among Women With or Without HIV in India

Abstract: Key Points Question Is elevated inflammation in pregnant women with or without HIV associated with adverse birth outcomes and infant growth deficits? Findings In this cohort study of pregnant women in Pune, India, higher levels during pregnancy of interleukin 17A were associated with increased odds of both preterm birth and low birth weight. Higher levels of interleukin 1β were associated with increased preterm birth and infant growth deficits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
(34 reference statements)
3
16
0
Order By: Relevance
“… 43 In contrast, a recent study in India among 218 women, 32% of whom were PWLHIV, found no associations between AGP or CRP and low birthweight or preterm birth, either overall or by maternal HIV status. 18 However, the same study found associations between increased interleukin-1β, another marker of systemic inflammation, and increased odds of preterm birth, both overall and among PWLHIV. 18 Other studies have also found high levels of CRP early in pregnancy to be associated with increased risk of preterm birth, as well as the risk of preeclampsia and growth restriction.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“… 43 In contrast, a recent study in India among 218 women, 32% of whom were PWLHIV, found no associations between AGP or CRP and low birthweight or preterm birth, either overall or by maternal HIV status. 18 However, the same study found associations between increased interleukin-1β, another marker of systemic inflammation, and increased odds of preterm birth, both overall and among PWLHIV. 18 Other studies have also found high levels of CRP early in pregnancy to be associated with increased risk of preterm birth, as well as the risk of preeclampsia and growth restriction.…”
Section: Discussionmentioning
confidence: 94%
“… 18 However, the same study found associations between increased interleukin-1β, another marker of systemic inflammation, and increased odds of preterm birth, both overall and among PWLHIV. 18 Other studies have also found high levels of CRP early in pregnancy to be associated with increased risk of preterm birth, as well as the risk of preeclampsia and growth restriction. 21 One reason for inconsistent findings on CRP between studies may be the timing of CRP measurement as well as the role of HIV which is known to contribute to heightened immune activation and inflammatory response even with ART.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Diet significantly contributes to increasing the pregnancy risk from early gestation [ 8 ], playing a key role in the regulation of chronic inflammation in pregnant and non-pregnant adults [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In fact, several high-quality studies, reviews, and meta-analyses have demonstrated that the Mediterranean diet (MD) is a healthy dietary pattern and that higher adherence to MD is associated with the prevention of several diseases and lower inflammatory levels [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%